Bentuk Pesan Komunikasi Organisasi Ikatan Pemuda Dalam Peningkatan Keamanan Dan Kenyamanan Warga Kota Padang - Nora Zulvianti; Gusti Indah Sari; Wakidul Kohar (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2021)
Communication is an activity that is always carried out in everyday life. It is carried out by individuals with individuals, individuals with groups (organizations) and groups with groups (organizations). Marapi gang youths have low awareness to provide security and comfort in their environment. communication between youth leaders and members is still not optimal. This makes the organization not run well. Young people are busy with their own business. The purpose of this study was to find out and understand the form of messages contained in the Gang Merapi Youth Association (IPPGM) Gunung Pangilun Village, North Padang District, Padang City. This research is a field research. The method used is a qualitative method. This type of research is descriptive. The approach is phenomenology. The findings of this study are the messages conveyed by the communicator to the communicant using clear and easy-to-understand language. In addition, the delivery of messages in the form of invitations and orders is also accompanied by body movements, facial expressions, symbolic clothing, sounds and symbols or other symbols that have meaning so that the intended message will be easy to understand